Kelimpahan Dan Distribusi Fitoplankton Di Wilayah Perairan Mangrove Morosari, Demak: Abundance And Distribution Of Phytoplankton In The Mangrove Water, Morosari, Demak - Oktavianto Eko Jati; Arif Rahman; Kukuh Prakoso (LPPM Universitas Mataram, 2022)
The Demak area is an area that has changed its ecological function from land to water. This area has a mangrove ecosystem which is a conservation area. The fertility of the mangrove ecosystem is supported by the presence of nutrients in the waters. Nutrients in the waters will also affect the abundance and distribution of phytoplankton. The purpose of this study was to determine the levels of nitrate, phosphate, and the abundance and distribution of phytoplankton in the Morosari Demak mangrove conservation waters, and to determine the relationship between the abundance of phytoplankton and the levels of nitrate and phosphate in the waters. This research was carried out in May 2018 in the Morosari waters area, Demak. The sampling location consisted of 6 stations. The variables measured in this study included dissolved oxygen, pH, salinity, water temperature, nitrate, phosphate, and abundance of phytoplankton. The results showed that dissolved oxygen levels ranged from 2.18-6.11 mgL-1, pH 6.12-7.38; salinity between 18.43-31.84 o/oo; water temperature between 27.18 - 30.43 °C, nitrate 0.0029-0.2495 mgL-1; phosphate 0.0013-0.11 mgL-1. The abundance of phytoplankton obtained from this study ranged from 5,700 – 24,942 cells L-1. The dominant type of phytoplankton came from the genus Guinardia (diatom class/Bacillariophyceae) which was found in all research sites